Nasoalveolar Molding (NAM) in Early Management for Newborn with Labiognatopalatoschizis - Raodah, Raodah; Sutiyo, Sutiyo; Dammar, Irfan (Indonesian Journal of Prosthodontic, 2021)
Patient’s chief complaint: A 1-week-old female infant with bilateral cleft lip and palate was referred to the Department of Prosthodontic, Hasanuddin University Dental Hospital. Her parents provided informed consent prior to her treatment. Her nutrition was managed through a nasogastric tube (NGT). The patient was in primary need of appliance that could support her feeding. Patient’s oral status: Intraoral examination revealed bilateral complete cleft lip and palate deformity diagnosed as bilateral complete labiognatopalatoschizis. Treatment plan: Fabrication of NAM to reduce the severity of the initial cleft deformity and to achieve better and more stable results in cleft lip and palate infants, in particularly advantageous to lengthen the deficient columella prior to the primary surgical repair of the lip and nose. Details of the therapy: Preliminary impression were done at the first appointment using custom tray and elastomeric impression material. At 2 weeks after birth, a conventional molding plate was fabricated on the maxillary cast obtained by preliminary impression. After the NAM was completed, try in was performed on the patient's mouth and adjustment were made to the edges of the NAM. Summary: Nasolalveolar molding (NAM) allows an overall improvement in functional activity thus increasing infant’s weight prior to surgery, also correct the aesthetics of the nasolabial complex in bilateral cleft conditions while minimizing the extent of the surgery and the overallnumber of surgical procedures.